O futuro da inserç\~ao internacional do Brasil: Quest\~oes para o desenvolvimento até 2035 - Raphael Camargo Lima (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– In Brazil, it has been difficult to elaborate governmental planning surpassing the four-year spectrum from the Pluriannual Plans. Despite the fact of long-term planning attracting a wide range of sectors, it still occupies a small space in both political and bureaucratic agendas. Hence, the present study proposes to initiate a new cycle of debates regarding the issue as it presents questions and factors to subsidy long-term strategies. Using methodological tools from Strategic Prospective, we present trends and uncertainties regarding Brazil's international insertion, contemplating topics such as the organization of the international system, foreign policy, international security and national defense. This study is part of Brasil 2035, a project whose objective is to provide subsidies to formulate long-term strategies for Brazil through Prospective Scenarios. Thus, this text presents a preliminary stage of a prospective process regarding the identification and analysis of the main variables. We do not intend to be conclusive, but rather to present some key factors and questions, which will affect Brazilian development until 2035.
Keywords: C53; F59; F02; K33; 330; strategic prospective; prospective scenarios; long-term planning; international relations; international insertion; regional integration; international security; national defense